2013
DOI: 10.1098/rsif.2013.0041
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of pearl oyster shell matrix proteins with repetitive, low-complexity domains

Abstract: The lysine (K)-rich mantle protein (KRMP) and shematrin protein families are unique to the organic matrices of pearl oyster shells. Similar to other proteins that are constituents of tough, extracellular structures, such as spider silk, shematrins and KRMPs, contain repetitive, low-complexity domains (RLCDs). Comprehensive analysis of available gene sequences in three species of pearl oyster using BLAST and hidden Markov models reveal that both gene families have large memberships in these species. The shematr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 39 publications
6
72
0
Order By: Relevance
“…In the present case, in spite of overall sequence similarities observed within these several RLCD protein categories identified in different models, it remains difficult to clearly outline whether they are true homologues considering the limitation of standard Blastp tools for low-complexity sequences, the fast rate of evolution of these domains [41,43] and that fortuitous low-complexity sequence similarities can be obtained between non-homologous SMPs that have evolved completely independently.…”
Section: Byssal Protein-like N- T- Q- G-and M-rich Proteinsmentioning
confidence: 93%
“…In the present case, in spite of overall sequence similarities observed within these several RLCD protein categories identified in different models, it remains difficult to clearly outline whether they are true homologues considering the limitation of standard Blastp tools for low-complexity sequences, the fast rate of evolution of these domains [41,43] and that fortuitous low-complexity sequence similarities can be obtained between non-homologous SMPs that have evolved completely independently.…”
Section: Byssal Protein-like N- T- Q- G-and M-rich Proteinsmentioning
confidence: 93%
“…By directly comparing the transcriptome of nacre-forming cells in a bivalve and gastropod, it has been revealed that there are tremendous differences in these secretomes, with less than 15% of secreted SMPs being shared (Jackson et al 2010). These differences also extend to comparisons between nacre-and prism-associated SMPs of two closely related pearl oyster species (P. maxima and P. margaritifera), and to comparisons within biomineralising gene families (shematrin and KRMP) across Pinctada species (Marie et al 2012b, McDougall et al 2013a, lending support to the supposition that mollusc shell formation is primarily controlled by rapidly evolving genes (Jackson et al 2006). …”
Section: Most Secreted Shell Matrix Proteins Are Encoded By Rapidly Ementioning
confidence: 80%
“…However, the true function of these RLCD-containing proteins in molluscan biomineralisation is still unknown because the behaviour of these motifs in vivo is likely to be affected by multiple factors and in vitro studies cannot inform us about the processes that occur within the complex shell environment. Nevertheless, given the high proportion of RLCD-containing proteins present in a wide range of shell-forming proteomes and transcriptomes (Jackson et al 2010, Marie et al 2010a, McDougall et al 2013a, Werner et al 2013, it is clear that these proteins are important shell components.…”
Section: Many Secreted Shell Matrix Proteins Are Characterised By Thementioning
confidence: 99%
See 2 more Smart Citations